THE INDIS STYLE: THE TRANSFORMATION AND HYBRIDIZATION OF BUILDING CULTURE IN COLONIAL JAVA INDONESIA - Djoko Sukiman; Bambang Purwanto (Paramita: Historical Studies Journal)
This historical study is focused on Indis style houses and buildings in Java during colonial period. The study discusses the reception and adaptation of Dutch and other cultures together with the local cultures in the transformation and hybridization of Indonesian architectural design production and reproduction. The study concludes that Indis style is a proof for the western inability to avoid the social and cultural influence of the locals, representations of new hybrid identities who want to show themselves as closer to the west and distance from the  indigenous, representation of new identity among those who found a new definite motherland since others consider themselves alien, symbol of modernity for those who were looking for a new social status and justify their existence, and a representation of the history of colonialism itself.